P130 Limits of agreement for peak expiratory flow measured by mini-Wright's meter and a pneumotachograph. (16th November 2010) - Oliver, S J; Ingram, E; Fynn, D; Urquhart, D S
Abstract : Background: Differences in peak expiratory flow (PEF) in children have been shown using a short exhalation PEF compared with a forced vital capacity (FVC) manoeuvre, when measured by turbine spirometry. Furthermore, PEF measures using a traditional Wright's scale PEF metre have been compared with those measured by FVC using a pneumotachograph in adults. The traditional Wright's scale may give rise to misleading results in children, and as such universal adoption of the EU scale has been advocated in the UK. To our knowledge, no study has compared PEF measured using a mini-Wright's EU scale PEF metre and PEF measured by FVC manoeuvres using a pneumotachograph in children. Methods: A retrospective review of children attending asthma clinic at a tertiary paediatric asthma clinic were carried out. Children underwent spirometry (Jaeger Masterscreen PFT Pro) using a pneumotachograph in accordance with ATS/ERS guidelines. In addition, peak expiratory flow (PEF) using a mini-Wright's PEF metre (Clement-Clarke International) was performed by each subject. Bland and Altman statistics were used to assess the limits of agreement for PEF measured by the two different techniques. Results: 161 children (90 male) aged 4–17 years with mean (sd) age of 10.1 (3.2) years were analysed. PEF measures varied from 87 to 613 l/min on spirometry, and from 100 to 570 l/min with the PEF metre. The mean (sd) difference between PEF measures by spirometry and PEF metre was 1.1 (23.5) l/min. A Bland-Altman plot showing mean (+/−2SD) difference is shown (Abstract P130 Figure 1 ). Discussion: Whilst close agreement for a childhood asthma population was demonstrated for two measures of PEF, individual differences could be quite marked with 100 l/min differences in PEF measurement being seen in either direction. One should be aware of potential differences in PEF measures when choosing testing equipment. Consideration should be given to dual measures of PEF in the setting of paediatric asthma (and not simply relying on a mini-Wright's PEF alone).